Transforming European Metropolitan Regions Smart mobility for better liveability - Nared, Janez (ZRC SAZU, Založba ZRC, 2019)
Transportation in urban areas, particularly metropolitan regions, generates congestion and vast greenhouse gas emissions, and thus imposes enormous challenges upon authorities in providing healthy living conditions and a supportive environment for businesses. Thus, the overall objective of the SMART-MR project was to support local and regional authorities in improving transport policies and providing sustainable measures for achieving resilient low-carbon transportation and mobility in metropolitan regions. To tackle this issue, ten project partners from eight metropolitan regions (Oslo, Gothenburg, Helsinki, Budapest, Ljubljana, Rome, Porto, and Barcelona) have shared their experience in transport and mobility planning by holding seven topically interrelated workshops. The goal of this publication is not to present all of the project results. It only focuses on the main lessons learned during the seven workshops.